Optimalisasi Pengelolaan Laporan Keuangan UMKM Berbasis Digital - Sindi Amelia; Ratri Paramitalaksmi (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This service program aims to provide training and assistance to Micro, Small and Medium Enterprises (MSMEs) actors at Rudy's Restaurant and Cafe Luku Ndalu, located in Karanglo Village, Argomulyo, Sedayu District, Bantul Regency, Yogyakarta. The main focus of the training was the preparation of digital-based financial reports using the Kledo application. This activity took place on September 2-6, 2024, through three stages: 1) survey, 2) training and mentoring, and 3) evaluation. Evaluation was carried out by comparing the results of the pre-test and post-test of the same 15 questions, as well as post-activity supervision. The results showed an increase in participants' understanding of MSME financial statements, from 25% to 95%. In addition, all participants understood the features of the Kledo application in depth, including how to use it, and successfully applied it in recording their business financial statements.